Computational analysis of double rotating cylinders for conceptual design of an estol, fixed wing UAV - Alias, Mohd Shahidi (2017)
Many efforts in Unmanned Aerial Vehicle (UAV) aerodynamic design technology led to a broad of additional applications. Magnus effect is the effect of moving airstream to the spinning ball or cylinder. Previous studies revealed the feasibility of Magnus effect on rotating cylinder producing lift which impacted an improvement of coefficient of forces. The studies have discovered the limitation of implementation caused by induced and parasite drag occurrences. These challenges addressed in this study to achieve the effect for lifting the body by mean of thinning the boundary layer of the air flow at the upper separation region of rotated cylinder. Accordingly, spin ratio, α and Reynold number, Re are the considerations in this study for optimization. The previous experimental and numerical data were used as a basis to conceptually design of an optimum rotating cylinder aerodynamic characteristics. 2D numerical is simulated using ANSYS FLUENT R15.0 to carefully examine for the coefficient of lift and drag while understanding the aerodynamic characteristics and flow field of the rotating cylinder surface body. Following the methodological approach as the evidences of the Magnus effect, Finite Volume Numerical Analysis method is used in this parametric study. Present work studied on Reynold number, 1 x 103 ≤ Re ≤ 5 x 105 and spin ratio ranging from 0 ≤ α ≤ 4.32 whereby the air velocity range within 3.65 ms-1 ≤ U∞ ≤ 29.208 ms-1. Lift Coefficient, CL and Drag Coefficient, CD determined in every stage analysis. The optimum CL based on the parametric study lead to the vital conclusion of concept design of ESTOL UAV fix wing application where the operating cylinders system are embedded inside the NACA airfoil.